Discovery of Novel and Clinically Relevant Markers in Formalin-Fixed Paraffin-Embedded Esophageal Cancer Specimen - Abdo, Joe; Wichman, Christopher S.; Dietz, Nicholas E.; Ciborowski, Pawel; Fleegel, John; Mittal, Sumeet K.; Agrawal, Devendra K. (Frontiers in Oncology, 2018)
Due to the ineffectiveness of chemoradiation and targeted therapy in esophageal anticancer care and the subsequent low survival rates, we constructed a high throughput method to discover and investigate new markers with prognostic, diagnostic, and therapeutic clinical utility. This was accomplished by developing a quick, inexpensive, and dependable platform to simultaneously quantify thousands of proteins which subsequently revealed novel markers involved in the pathogenesis of esophageal adenocarcinoma (EAC) via discovery mass spectrometry paired with conservative biostatistics. Our method uncovered a perfect storm of tumor suppressors being downregulated, proliferation markers ramped up, and chemoresistance markers overexpressed—many of which could serve as new therapy targets for EAC. The 12 markers discovered by this method are novel regarding their involvement in the pathogenesis of EAC. The molecular oncology arena now has a dozen new proteomic targets suitable for validation and elucidation of their clinical utility via gene knockdown in cellular and animal models. This new method can be replicated and applied to other cancers or disease states for research and development and discovery-based investigations. Our findings, which serve as a proof of concept, will hopefully motivate research groups to further expound on the molecular processes involved in the aggressiveness of EAC and other solid tumor diseases, ultimately leading to improved patient management strategies.